Tidal-influenced transgression processes in late cretaceous Termit Basin, Niger - Yuan, ShengQiang; Yu, Chengqian; Zhang, Xingyang; Zhai, Guanghua; Steel, Ronald J.; Chen, Si; Wang, Hairong; Jiang, Hong; Song, Yifan; Song, Jinyan (Frontiers in Earth Science, 2025)
Tidal characteristics observed in sediment cores serve as significant indicators of marine paleo-environments. In order to comprehend the sedimentary processes taking place in the Termit Basin and its connections with the New Tethys and the southern Atlantic Ocean during the Late Cretaceous, a comprehensive array of sedimentological and petrographic analyses have been performed on the core data, thin sections, seismic data, paleontological fossils, and drilling samples from the Termit Basin. New insights into tidal sedimentary processes were obtained through this research, and sedimentological evidence for the development of transgressive sequences in the study area was established. Analysis of lithofacies, paleontological fossils, and fossil contents shows that the Termit, Iullemeden, Tefidet, and Tenere basins together formed a unified sedimentary basin in the Late Cretaceous. Well correlation and seismic profiling analysis also confirm this view. The unified sedimentary basin was connected to the northern New Tethys and the southern Atlantic Ocean. Stratigraphic analyses revealed that the Late Cretaceous of the Termit Basin underwent a complete episode of marine transgression. The discovery of Tidal features such as bidirectional cross-bedding and double mud drapes in Late Cretaceous Yogou Formation cores in the Termit Basin provide compelling evidence of their connection to the central Saharan Seaway, suggesting that the sedimentary basin was connected to the northern New Tethys and the South Atlantic Ocean. This study also explores the source supply system, development features of carbonate rock, the prototype basin, and the hydrocarbon exploration potential of the Late Cretaceous Termit Basin. The results of this study reveal the following: (i) the Late Cretaceous Yogou Formation in the Termit Basin exhibits well-developed tidal processes; (ii) an extensive transgression occurred, encompassing a series of basins in eastern Niger, which led to the inclusion of these areas within the Saharan Seaway during the Late Cretaceous; (iii) the deposition of mudstone over a wider area of the Late Cretaceous Termit Basin, indicating the existence of more source rocks and resources to be developed.